The optical performance of holmium oxide doped tellurite glass for potential optical fiber - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2021)
The optical performance of holmium oxide doped tellurite glass for potential optical fiber by Muhammad Noorazlan Abd Azis